The Central Dark Matter Fraction of Massive Early-Type Galaxies - Tortora, C.; Napolitano, N. R. (Frontiers in Astronomy and Space Sciences, 2022)
Dark matter (DM) is predicted to be the dominant mass component in galaxies. In the central region of Early-type galaxies it is expected to account for a large amount of the total mass, although the stellar mass should still represent the majority of the mass budget, depending on the stellar Initial Mass Function (IMF). We discuss latest results on the DM fraction and mean DM density for local galaxies and explore their evolution with redshifts in the last 8 Gyr of the cosmic history. We compare these results with expectations from the $Λ$CDM model, and discuss the the role of the IMF and galaxy model, through the central total mass density slope. We finally present future perspectives offered by next generation instruments/surveys (Rubin/LSST, Euclid, CSST, WEAVE, 4MOST, DESI), that will provide the unique chance to measure the DM evolution with time for an unprecedented number of galaxies and constrain their evolutionary scenario.